Răspuns:
Explicație pas cu pas:
a) a = - 13
a × b + a = - 182
→ a = factor comun
a × ( b + 1 ) = - 182
( - 13 ) × ( b + 1 ) = - 182
b + 1 = ( - 182 ) : ( - 13 )
b + 1 = 14
b = 14 - 1
b = 13
___________________________________
b) a = - 14
a × b + a × c = 182
a × ( b + c ) = 182
( - 14 ) × ( b + c ) = 182
b + c = 182 : ( - 14 )
b + c = 13 → suma
______________________________
c) b + c = 15
a × b + a × c + 15 × a = - 3 510
a × ( b + c + 15 ) = - 3 510
a × ( 15 + 15 ) = - 3 510
a × 30 = - 3 510
a = ( - 3 510 ) : 30
a = - 117